Application of Good Processed Food Production Method (CPPOB) for BPOM distribution license certification - Miftakhur Rohmah; Safira Fadhila; Anton Rahmadi; Yulian Andriyani (University of Merdeka Malang, 2023)
The Good Processed Food Production Method (CCPOB) or Good Manufacturing Practices (GMP) is a guideline used in every processing activity of small and large industries in order to produce products that are of good quality, safe, and suitable for consumption. Along with the increasing growth of processed food MSMEs in Indonesia, many business actors still pay less attention to food safety in producing a product. One of them is that business actors have not implemented the Good Processed Food Production Method (CPPOB) in accordance with the standards. Therefore, assistance is needed for MSMEs Dapoer Ikan Diana in implementing CPPOB in production facilities and preparing requirements for fulfilling the MD product distribution permit. This community service activity is implemented through several stages: data collection, assistance, monitoring, and evaluation. Based on the results of this community service activity, the application of CPPOB in the production facilities of MSMEs Dapoer Ikan Diana has met the standards. This allows MSMEs to apply for the issuance of MD product distribution permits.